Impact of inhalational exposure to ethanol fuel on the pharmacokinetics of verapamil, ibuprofen and fluoxetine as in vivo probe drugs for CYP3A, CYP2C and CYP2D in rats - Cavalcanti Cardoso, Juciane Lauren; Lanchote, Vera Lucia; Marques Pereira, Maria Paula; Vieira Capela, Jorge Manuel [UNESP]; Moraes, Natalia Valadares de [UNESP]; Lepera, Jose Salvador [UNESP] (Elsevier B.V., 2015)
Occupational toxicology and clinical pharmacology integration will be useful to understand potential exposure-drug interaction and to shape risk assessment strategies in order to improve occupational health. The aim of the present study was to evaluate the effect of exposure to ethanol fuel on in vivo activities of cytochrome P450 (CYP) isoenzymes CYP3A, CYP2C and CYP2D by the oral administration of the probe drugs verapamil, ibuprofen and fluoxetine. Male Wistar rats exposed to filtered air or to 2000 ppm ethanol in a nose-only inhalation chamber during (6 h/day, 5 days/week, 6 weeks) received single oral doses of 10 mg/kg verapamil or 25 mg/kg ibuprofen or 10 mg/kg fluoxetine. The enantiomers of verapamil, norverapamil, ibuprofen and fluoxetine in plasma were analyzed by LC-MS/MS. The area under the curve plasma concentration versus time extrapolated to infinity (AUC(0-infinity)) was calculated using the Gauss-Laguerre quadrature. Inhalation exposure to ethanol reduces the AUC of both verapamil (approximately 2.7 fold) and norverapamil enantiomers (>2.5 fold), reduces the AUC(0-infinity) of (+)-(S)-IBU (approximately 2 fold) and inhibits preferentially the metabolism of (-)-(R)-FLU. In conclusion, inhalation exposure of ethanol at a concentration of 2 TLV-STEL (6 h/day for 6 weeks) induces CYP3A and CYP2C but inhibits CYP2D in rats. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Ethanol fuel; Inhalation; Pharmacokinetics; CYP3A; CYP2C; CYP2D